Mitochondrial ROS and the Effectors of the Intrinsic Apoptotic Pathway in Aging Cells: The Discerning Killers! - Hekimi, Siegfried; Wang, Ying; Noë, Alycia (Frontiers in Genetics, 2016)
It has become clear that mitochondrial reactive oxygen species (mtROS) are not simply villains and mitochondria the hapless targets of their attacks. Rather, it appears that mitochondrial dysfunction itself and the signaling function of mtROS can have positive effects on lifespan, helping to extend longevity. If events in the mitochondria can lead to better cellular homeostasis and better survival of the organism in ways beyond providing ATP and biosynthetic products, we can conjecture that they act on other cellular components through appropriate signaling pathways. We describe recent advances in a variety of species which promoted our understanding of how changes of mtROS generation are part of a system of signaling pathways that emanate from the mitochondria to impact organism lifespan through global changes, including in transcriptional patterns. In unravelling this, many old players in cellular homeostasis were encountered. Among these, maybe most strikingly, is the intrinsic apoptotic signalling pathway, which is the conduit by which at least one class of mtROS exercise their actions in the nematode Caenorhabditis elegans. This is a pathway that normally contributes to organismal homeostasis by killing defective or otherwise unwanted cells, and whose various compounds have also been implicated in other cellular processes. However, it was a surprised that that appropriate activation of a cell killing pathway can in fact prolong the lifespan of the organism. In the soma of adult C. elegans, all cells are post-mitotic, like many of our neurons and possibly some of our immune cells. These cells cannot simply be killed and replaced when showing signs of dysfunction. Thus we speculate that it is the ability of the apoptotic pathway to pull together information about the functional and structural integrity of different cellular compartments that is the key property for why this pathway is used to decide when to boost defensive and repair processes in irreplaceable cells. When this process is artificially stimulated in mutants with elevated mtROS generation or with drug treatments it leads to lifespan prolongations beyond the normal lifespan of the organism.